Patient perspectives on the use of half-unit insulin pens by people with type 1 diabetes: a cross-sectional observational study. (2nd January 2021) - Piras de Oliveira, Carolina; Mitchell, Beth D.; Fan, Ludi; Garey, Colleen; Liao, Birong; Bispham, Jeoffrey; Vint, Nan; Perez-Nieves, Magaly; Hughes, Allyson; McAuliffe-Fogarty, Alicia
Abstract: Background: Half-unit pens offer the ability to dose insulin more precisely. Information about half-unit pen use and evidence of their benefits and drawbacks is limited. This study aims to characterize people with type 1 diabetes (T1D) who have used (current/former = EVER) vs. those who have never used half-unit pens (NEVER users) and to understand their perspective. Methods: An observational cross-sectional online survey was administered through T1D Exchange's online patient community, myGlu.org, to understand the use of half-unit insulin pens. Results: The 278 adult participants (156 EVER, 122 NEVER) had a mean age of 41.8 ± 12.7 years, body mass index of 26.0 ± 3.8 kg/m 2, glycated hemoglobin of 6.3% ± 1.0%, and 55% were male. EVER users had T1D for a shorter duration than NEVER users ( p < .001). EVER users were less likely to use continuous subcutaneous insulin infusion ( p < .001) and more likely to start correcting high blood glucose at a lower level ( p < .001) and low blood glucose at a higher level ( p < .001). The highest ranked benefits of half-unit pen reported by its current users ( N = 131) included prevention of hyperglycemia (40.5%), less anxiety or worry (23.7%), and prevention of hypoglycemia (16.8%). Conclusions: Half-unit insulin pen is perceived as an insulin device that may help people with T1D to avoid hypo- and hyperglycemic events and decrease their level of disease worry and anxiety. This study highlights the need for patients and health care providers to understand the benefits of half-unit pens while considering options for individualized diabetes management.